Testing the Range and Analysis of WSN LoRa Sx1278 Parameters in Coastal Areas - Kusuma, Hollanda Arief; Hanafi, M Fadzil; Suhendra, Tonny; Oktaviani, Nadya (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2024)
This research discusses the testing of the range and analysis of other parameters of Wireless Sensor Network (WSN) technology using LoRa technology at 433 MHz frequency in coastal areas. This study aims to provide important information for the development of WSN and LoRa technology, especially in coastal areas. The research method used is the design of the device, the creation of transmitter and receiver firmware, and field testing using the continuous method in Teluk Sebong, Berakit on May 26, 2022. The results showed that the maximum range achieved by the receiver was 7.3 km with a packet loss of 56.84%. Data transmission using LoRa experienced a significant delay, especially at a range of 4.2 km with a delay time of up to 18 seconds. In addition, the study also analyzed the LoRa network performance, such as the map of measurement and data loss points, the distribution of RSSI values, and the distribution of SNR values divided into several distance ranges. This research is expected to provide important information for the development of WSN and LoRa technology, especially in coastal areas